COMPARING FLUORIDE REMOVAL KINETICS OF ADSORPTION PROCESS FROM AQUEOUS SOLUTION BY BIOSORBENTS - Singh, Tej Pratap; Cb, Majumder (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: In this study, we observed the defluoridation capacity of groundnut shell and Citrus limetta (commonly known as sweet lime) and aims at comparison of their defluoridation capacity. Methods: Batch experiments were carried out for this investigation. To find out the best operating conditions for maximum fluoride removal, we varied the contact time by keeping others parameters to be constant and observed their effects on defluoridation capacity. In this study to follow adsorption process, we used various kinetic models, namely, Elovich equation, Weber and Morris intra-particle diffusion model, Bangham's pore diffusion model, and the pseudo first and second order equations. We also calculated and discussed the effects of various kinetic parameters such as correlation coefficients, equilibrium adsorption capacities and rate constant. Results: The hand-in-hand relationship between intra-particle diffusion model and Elovich equation indicates a major role of pore diffusion process in adsorption mechanism. Furthermore, the rate kinetics is best described by pseudo second order model for both the biosorbents. Conclusion: From the performed experiments, it was found that Citrus limetta peel has more defluoridation capacity in comparison of groundnut shell in all manners. Keywords: Adsorption kinetics, Adsorption, Biosorbent, Ground nut shell, Citrus limetta peel.